2021
DOI: 10.21037/cdt-21-147
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitor-induced fulminant myocarditis, complete atrioventricular block and myasthenia gravis—a case report

Abstract: 4 (CTLA-4), programmed death 1 (PD-1) or its ligand, programmed death-ligand 1 (PD-L1). There are currently seven FDA-approved ICIs for cancer therapy, which include ipilimumab (anti-CTLA-4), nivolumab, pembrolizumab, cemiplimab (anti-PD-1), avelumab, atezolizumab and durvalumab (anti-PD-L1). However, these drugs may induce inflammatory side effects as a result of the increased immune system activity, which are generally termed as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Considering steroids as the main treatment for immune myocarditis, we also summarized new immune checkpoint inhibition into the biologic agent category in Table 2 , including six case-use reports of infliximab, one case of anti-thymocyte globulin (ATG), and one case of abatacept. Two studies reported nonsignificant improvement in symptoms related to myocarditis with infliximab ( 51 , 52 ), while three cases reported a worsening manifestation of symptoms related to myocarditis with infliximab ( 53 55 ), and another study reported the use of infliximab but not describing the results ( 26 ). One study found the use of ATG was suspended due to poor patient status ( 56 ), and another study reported the myocarditis symptoms were improved with the use of Abatacept ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering steroids as the main treatment for immune myocarditis, we also summarized new immune checkpoint inhibition into the biologic agent category in Table 2 , including six case-use reports of infliximab, one case of anti-thymocyte globulin (ATG), and one case of abatacept. Two studies reported nonsignificant improvement in symptoms related to myocarditis with infliximab ( 51 , 52 ), while three cases reported a worsening manifestation of symptoms related to myocarditis with infliximab ( 53 55 ), and another study reported the use of infliximab but not describing the results ( 26 ). One study found the use of ATG was suspended due to poor patient status ( 56 ), and another study reported the myocarditis symptoms were improved with the use of Abatacept ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our results suggested that the use of PD-1, PD-L1 or CTLA4 inhibitors in the treatment of patients with advanced TETs required close attention on the generation of immune-related adverse reactions such as MG while treating tumors. Anti-PD-L1 or anti-PD-1 antibodies have been reported to cause adverse reactions such as MG, myocarditis and pneumonia in patients with TETs [ 32 35 ]. Further, our study provides multiple potential immunotherapeutic targets such as CD2.…”
Section: Discussionmentioning
confidence: 99%
“…These immune-related adverse events most commonly involve hepatitis, colitis, myocarditis and dysregulations of endocrine systems including the pancreas and adrenal glands ( 52 ). Interestingly, several reports showed that ATG is able to counteract adverse events caused by immune checkpoint inhibition ( 53-55 ). While this effect is in part explainable by its T-cell depleting properties, based on our data, it is tempting to speculate that induction of PDL-1 on monocytes, or other cell types, potentially contributes to the inhibition of autoreactive T-cells, resulting in an amelioration of the reported adverse effects.…”
Section: Discussionmentioning
confidence: 99%